The influence of blood pressure on trans-synovial flow in the rabbit. - Knight, A D (1984)
Fluid exchange across the synovium lining the cavity of extended knees was studied in twenty rabbit hindquarters. The isolated hindquarters were perfused with blood from an extracorporeal pump-oxygenator system at controlled arterial pressure (PA) and venous pressure (PV). Intra-articular pressure (PJ) was set at 18 cmH2O in most experiments. The rate of trans-synovial absorption of Krebs solution (QS), measured by a drop-counter, was a negative linear function of PA (70-160 mmHg) and of PV (2-42 cmH2O). The sensitivity of exchange to venous pressure ( dQS / dPV , mean -0.25 +/- 0.03 microliter min-1 mmHg-1) was greater than its sensitivity to arterial pressure ( dQS /dPA, mean -0.17 +/- 0.02 microliter min-1 mmHg-1). The ratio of the slopes, ( dQS / dPV )/( dQS /dPA), indicated the pre- to post-capillary vascular resistance ratio. From this ratio and PA, PV, synovial capillary pressures PC were calculated by the equation of Pappenheimer & Soto - Rivera (1948). Trans-synovial absorption rate was a negative linear function of PC. This observation supports the application to the synovial cavity of Starling's hypothesis for fluid exchange between interstitial spaces and plasma (Starling, 1896). The slope dQS /dPC equalled the net hydraulic conductance of the blood-joint barrier (synovium plus capillary endothelium), and averaged -0.425 +/- 0.025 microliter min-1 mmHg-1 at PJ = 18 cmH2O. When PJ was subatmospheric, as is common in extended normal joints, fluid exchange (measured indirectly as dPJ /dt) was only approximately 1/4 as sensitive to blood pressure as at PJ = 18 cmH2O. This observation supported the view that the conductance of the blood-joint barrier depends on PJ.